LIG/ZnO/Porphyrin-Functionalized EGFET-Based Electronic Tongue - Kishore Pushparaj; Alexandro Catini; Rosamaria Capuano; Leonardo Papale; Valerio Allegra; Gabriele Magna; Gianni Antonelli; Eugenio Martinelli; Yuvaraj Sivalingam; Roberto Paolesse; Corrado di Natale (Proceedings)
The use of laser cutter machines to produce porous graphene films is an innovative method for a low-cost production of flexible electrodes for electronics and sensing applications. Here, laser-induced graphene (LIG) is used to produce the gate electrodes of EGFET sensors. LIG electrodes and LIG electrodes functionalized with ZnO and metalloporphyrin-coated ZnO are used as elements of the electronic tongue. The array is tested in a classical experiment aimed at identifying complex food matrices, such as fruit juices. The results demonstrate the feasibility of the approach and provide a solid basis for further array developments.